Equivalent description and stability analysis for discrete-time systems with uniformly distributed uncertainty. (May 2022) - Cong, Shen
Abstract: We are concerned with discrete-time systems with uncertainty, which is assumed to be uniformly distributed over the unit interval [ 0, 1 ] . To describe this uncertainty, the space { 0, 1 } N, which is composed of all the infinite 0 - 1 sequences and endowed with the Haar measure, actually constitutes the underlying probability space. Therefore, it is shown that for stability analysis, such an uncertain system can be transformed into a switching system with switching sequences having maximal entropy. A stability criterion then is derived from this transformation. An illustrative example is included to show the effectiveness of the theoretical results.